Visual literacy in adult basic education : a study of ABET learners' visual perception with regard to their general level of English second language learning - Bouwer, Anne Margaret (Rhodes University, Faculty of Education, Department of Education, 2000)
Adult learners face many difficulties in their learning programmes, particularly due to the fact that having mastered literacy in their mother tongues, they move on to further educational programmes which are mostly produced in English. In contemporary society, people need to be adept in a number of literacies, termed multiliteracies. Adult learners are rarely taught visual competence as visual images are relegated to illustrations for written texts, and attention is mainly focussed on the all-important written word. Adult basic education learners need to be able to interpret pictures in books, newspapers and magazines, just as much as they need to be able to read and write. It is the premise of this research that visual literacy enhances thinking skills and that adult learners need to be actively taught how to interpret visual images in order to more ably deal with the written word, the more 'important' part of literacy. The goals of this research are to develop understanding of the processes which go into understanding images and text, and to examine how pictures can be used to help adult learners develop proficiency in English. Another goal is to teach learners the basics of visual literacy so as to improve their comprehension of the plethora of images surrounding them. The research findings could help to inform adult educators facing the current crisis in Adult Basic Education and Training in South Africa, focusing on a little-studied aspect of literacy, visual literacy, one of the critical outcomes in the new South African curriculum for Adult Education and one of the multiliteracies required by citizens of today's world.
Keywords: English language -- Study and teaching (Secondary) -- Foreign speakers; Visual literacy -- South Africa; Adult education -- South Africa